Anthropometrical and Physiological Determinants of Laboratory and on-Snow Performance in Competitive Adolescent Cross-Country Skiers - Sollie, Ove; Losnegard, Thomas (Frontiers in Physiology, 2022)
Purpose: To explore the anthropometrical and physiological determinants of laboratory and on-snow performance in competitive adolescent cross-country skiers. Methods: Fifty-two adolescent (25 girls) (14.8 ± 0.6 years) skiers performed an uphill treadmill rollerski session using the G2 ski skating technique. Gross efficiency (GE) was calculated from a submaximal work bout ( 84% of peak oxygen uptake; V̇O2peak) while V̇O2peak, accumulated oxygen deficit (ΣO2def) and laboratory performance were determined from a 3-min time trial (TT3min) before upper- and lower-body maximum strength were tested. Pearson’s product moment correlations and multiple regression analysis explored the relationship with anthropometrical and physiological determinations of laboratory and on-snow performance in sprint ( 1 km, 2.5-3 min) and distance races (5-7.5 km, 12-20 min) from the national championship for this age-group. Results: A large correlation was found between on-snow sprint and distance performance (boys r=.61, girls r=.76, both P<.01) and for on-snow distance performance with TT3min (r=.51 to .56, P<.05). V̇O2peak, ΣO2def and GE explained 80% of variations in performance in the TT3min, but substantial lower on-snow skiing performance ( 20-30%). For the TT3min performance, V̇O2peak showed a very large and large correlation for boys and girls (r=.76 and .65 respectively, both P<.01) and ΣO2def showed a large correlation for boys and girls (r=.53 and .55 respectively, both P<.01). Age showed a large correlation for boys (r=.56, P<.01), with no significant correlation for girls (r=-.19). For on-snow distance performance, V̇O2peak showed a large correlation for boys (r=.53, P<.01) and girls (r=.50, P<.05). For on-snow sprint performance, upper-body strength (r=.55, both sexes P<.01) and body mass index (BMI) showed a large correlation for boys (r=.53, P<.01) and girls (r=.51, P<.05). Conclusion: V̇O2peak is the most important determinant for overall XC skiing performance in competitive male and female adolescent skiers. However, upper-body strength and BMI correlate the most with sprint performance. While laboratory performance can be explained by physiological factors, on-snow-performance for adolescents is based on multivariate factors, implying the need for a holistic approach to understanding the sport-specific demands in such age-groups.